The geography of the continuum of entrepreneurship activities—a first glance based on German data - Sven Wolff; Christina Guenther; Petra Moog; David B. Audretsch (The Journal of Technology Transfer, 2022)
The characterization of how entrepreneurial a region or country is, has generally been shaped by a narrow view of what actually constitutes entrepreneurship. In the case of Germany, this has led to a characterization of Germany as not being particularly entrepreneurial. Such a view is at odds with the remarkable, high-performing family business, widely held to be the backbone of the economy. The purpose of this paper is to suggest that the interpretation prevalent in entrepreneurship literature is problematic due to a too narrow operationalization of the entrepreneurship concept. As Zahra ( 150 ; 2014) emphasized, context matters for entrepreneurship, especially on a local or spatial level. One particular organizational manifestation of entrepreneurship, family business, may be congruent in specific spatial and institutional contexts but not in others. Other geographic and institutional contexts may be congruent with the contrasting startups. Thus, an important and novel contribution of this paper is to analyze the geography of family business as distinct from startups: two ends of the entrepreneurship continuum, embedded in different kinds of entrepreneurial ecosystems. We generate innovative maps working with official data, showing the distinct distribution of both kinds of entrepreneurship in different ecosystems. These findings are connected with spatial effects, living conditions and lead to recommendations for policy measures. The paper focuses on Germany, because startups as well as family business are prevalent and can be found in all regions.
Keywords: L26; R11; M14; D21; E1; R12; 600; Family Business; Startups; Context; Regions; Sustainability; Policy; Ecosystem